MORPHOAGRONOMIC AND SENSORY PERFORMANCE OF COFFEE CULTIVARS IN INITIAL STAGE OF DEVELOPMENT IN CERRADO MINEIRO - Pereira, Dyanna Rangel; Aguiar, João Augusto Rodrigues; Nadaleti, Denis Henrique Silva; Fassio, Larissa de Oliveira; Carvalho, João Paulo Felicori; de Carvalho, Samuel Pereira; Carvalho, Gladyston Rodrigues (Coffee Science - ISSN 1984-3909, 2019)
Despite the great diversity of available Arabica coffee cultivars it is observed that, even when presenting different phenotypes of interest, new cultivars are adopted at a slow pace by coffee growers. One possible reason may be the lack of information on the performance of these genotypes in different regions and culture conditions. The aim this work was to verify the performance of twelve coffee cultivars in relation to morphoagronomic characteristics at initial stage of development, as well as the beans quality, in a condition of typical cultivation of the Cerrado. The trial was carried out in the municipality of Monte Carmelo - MG, in randomized block design, with four replicates. Morphoagronomic characteristics were evaluated 15 months after the implantation of the crop. The productivity and, subsequently, the quality of the beans, were evaluated at 18 months. Statistical analyzes were performed using the Genes software. The data were submitted to analysis of variance. The F test was used to determine the significance of treatments. The means were grouped by the Scott-Knott test (1974) at 5% probability and the experimental precision was verified by the estimation of the experimental variation coefficient (CV) and the selective accuracy. The sensory attributes were evaluated in a radar diagram, called “Sensogram”. Genetic variability was observed among cultivars for the vegetative characters. The cultivars Catuaí Vermelho IAC 144 and MGS Aranãs stood out as more productive, with a high percentage of sieve 16 and above and low percentage of grain type mocha. All the cultivars stood out as special, with emphasis on the cultivar Bourbon Amarelo IAC J10 in the wet processing and Catuaí Vermelho IAC 144 in the natural processing.